Examining the regional economic growth convergence in the Philippines using panel data - Lwin, Aye Aye
Abstract (In the Philippines, the level of economic activities has been unequal within the regions and that the level of regional economic activity has been predominantly unequal through the years. This study examines separate two parts. The first one is to identify the factors that contribute to the growth of the regional income in the country and the second part is to answer the research questions (a) Is the convergence in the growth rates of the different regions of the country? (b) Can laggard regions eventually catch up with the leading regions in term of growth? (c) What are the factors that hinder laggard regions to growth faster? Utilizing, regression, random effect model, this study analyzed the panel data from 2000 to 2015 of Family Income and Expenditure Survey (FIES) years such as 2000, 2993 until 2015. The data is secondary data and come from the Philippines Statistics Authorities, and under laggard regions to growth faster to in the country. Moreover, the convergence is in the growth rate of the different regions of the country. However, laggard regions eventually can't catch up with the leading regions in terms of growth).